The Influence of Different Factors on the Dual Atmosphere Effect Observed for AISI 441 Interconnects Used in Solid Oxide Fuel Cells. (10th July 2019) - Goebel, Claudia; Bo, Caterina; Svensson, Jan-Erik; Froitzheim, Jan
Abstract : Interconnects used in solid oxide fuel cells are subjected to dual atmosphere corrosion at 600 °C. In this work we show that the dual atmosphere effect is dependent on the thickness of the steel sheet. For this AISI 441 with varying thicknesses was exposed to dual atmosphere at 600 °C for 336 h. Before and after exposure photographs were taken to analyze the progress of corrosion on the air-facing side of the steel samples. Additionally, scanning electron microscopy and energy dispersive x-ray diffraction (SEM/EDX) analysis was conducted on all exposed samples. It was found that thinner samples showed increased breakaway oxidation than thicker samples.